Christianity in the north eastern hills of South Asia : social impact and political implications - Quarishi, Ferdaus A. (Ferdaus Ahmad) (Dhaka, Bangladesh : University Press, 1987)
With reference to north-eastern India and Chittagong Hills of Bangladesh.
Includes bibliographical references.
Keywords: Christianity -- India, Northeastern; Christianity -- Bangladesh -- Chittagong Hill Tracts (Region)